MORPHOLOGICAL DIVERSITY AND DISTRIBUTION OF BLAPS SCABRIUSCULA MÉNÉTRIÉS, 1832 (COLEOPTERA: TENEBRIONIDAE) - I. A. Chigray; G. M. Abdurakhmanov; M. V. Nabozhenko; V. Yu. Shmatko (Юг России: экология, развитие, 2016)
Aim. Distribution, habitats and morphological variability of two subspecies of the endemic Caucasian species Blaps scabriuscula Ménétriés, 1832 are considered in the paper.Results and main conclusions. Nominotypical subspecies is very rare and inhabits deserts of eastern Azerbaijan (Gobustan). The subspecies Blaps scabriuscula subalpina is distributed in the Eastern and the Central Caucasus and inhabits steppe and alpine landscapes to 3000 m. Several morphological forms are separated from the Central (North Ossetia, Kabardino-Balkaria, KarachayCherkessia) and the Eastern Caucasus (Chechnya, Dagestan, southern slopes of the Big Caucasus from Azerbaijan to Georgia – Khevsureti). Blaps scabriuscula subalpina is found in Rostov-on-Don (the first record for Rostov Region) in sandy soil meadow during building works. Rostov population is morphologically differs from Caucasian populations of the species. It is assumed that this record is associated with the ancient human migrations because of many representatives of this species-group (B. mortisaga (Linnaeus, 1758), B. puella Allard, 1880, B. scabriuscula, B. kovali Abdurakhmanov, Nabozhenko, 2011) have a propensity to synanthropy. Morphological description of Rostov population and differential characters of Caucasian populations are given. Female genital tubes of different populations of B. scabriuscula are described and figured for the first time. Nominatypical subspecies is strongly differs from other Caucasian Blaps Fabricius, 1775 in the structure of female genital tubes.